2020
DOI: 10.1089/neu.2019.6498
|View full text |Cite
|
Sign up to set email alerts
|

TMEM176A and TMEM176B Are Candidate Regulators of Inhibition of Dendritic Cell Maturation and Function after Chronic Spinal Cord Injury

Abstract: Inhibition of dendritic cell maturation and activation, together with abnormal functioning of cell-mediated immunity, has been reported in chronic spinal cord injury (SCI). The development of immune-based therapies could: 1) prevent or slow down limit further tissue damage in chronic SCI, and 2) promote tissue regeneration. To identify novel candidate molecular pathways mediating SCI-induced immune changes, we performed whole-genome microarray and molecular pathway analyses. Subjects with motor complete chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…Chromosome X Open Reading Frame 21 (CXorf21) has been observed to be a susceptibility gene in SLE ( 34 ), and here, Chromosome 11 Open Reading Frame 31 ( C11orf31 ) and Chromosome 1 Open Reading Frame 162 ( C1orf162 ) were broadly expressed in subtypes of T and B cells and monocytes. TMEM176A and TMEM176B , which were suggested to inhibit DC maturation in chronic spinal cord injury ( 35 ), were expressed in three subtypes of monocytes. Genome-wide association studies (GWASs) reported that the genetic locus of most MHC regions, such as HLA-DQB1 , HLA-DRA1 , HLA-DQA1 , were associated with pSS ( 36 ).…”
Section: Resultsmentioning
confidence: 99%
“…Chromosome X Open Reading Frame 21 (CXorf21) has been observed to be a susceptibility gene in SLE ( 34 ), and here, Chromosome 11 Open Reading Frame 31 ( C11orf31 ) and Chromosome 1 Open Reading Frame 162 ( C1orf162 ) were broadly expressed in subtypes of T and B cells and monocytes. TMEM176A and TMEM176B , which were suggested to inhibit DC maturation in chronic spinal cord injury ( 35 ), were expressed in three subtypes of monocytes. Genome-wide association studies (GWASs) reported that the genetic locus of most MHC regions, such as HLA-DQB1 , HLA-DRA1 , HLA-DQA1 , were associated with pSS ( 36 ).…”
Section: Resultsmentioning
confidence: 99%
“…To further determine the specific roles of potential transcripts that might contribute to CVB3 pathogenesis, we performed DGE in fibroblast clusters 1, 5, 6, and 8 of myocarditis and control ( Fig 4D ). These analyses revealed increased expression of complement proteins C3 and C4b ; Serpina3n, an accelerator of wound healing 53 ; Tmem176b , which controls DC maturation and also has a role in fibrosis 54 ; Tmem176a a negative regulator of DCs 55 ; and the anti-viral protein Ifitm 56 in all clusters of myocarditic mice ( Fig 4D ). Uniquely however, Sbno2 , a regulator of proinflammatory cascade 57 and Ly6a, also called Sca-1 , which has a known function in heart failure 58 , were increased in cluster 1 of myocarditic mice, as opposed to Gsta3, an inhibitor of TGF-β-induced epithelial and mesenchymal transition and fibronectin expression 59 , and Socs3 29 in cluster 5; Apod 52 in cluster 6; and Apoe in cluster 8 of myocarditic mice ( Fig 4D ).…”
Section: Resultsmentioning
confidence: 92%
“…Serpina3n, an accelerator of wound healing 53 ; Tmem176b, which controls DC maturation and also has a role in fibrosis 54 ; Tmem176a a negative regulator of DCs 55 ; and the anti-viral protein Ifitm 56 in all clusters of myocarditic mice (Fig 4D). Uniquely however, Sbno2, a regulator of proinflammatory cascade 57 and Ly6a, also called Sca-1, which has a known function in heart failure 58 , were increased in cluster 1 of myocarditic mice, as opposed to Gsta3, an inhibitor of TGF-β-induced epithelial and mesenchymal transition and fibronectin expression 59 S3).…”
mentioning
confidence: 99%
“…For example, accumulating evidence reported that Tmem176a was involved in the remodeling of the dendritic cell after spinal cord injury. 23 Dendritic cells play a central role not only in the development of innate and adaptive immunity but also in the induction and maintenance of immune tolerance. 24 Previous studies showed that Tmem176a and Tmem176b could inhibit dendritic cell maturation and activation, together with abnormal functioning of cell‐mediated immunity.…”
Section: Discussionmentioning
confidence: 99%